Development of a New Validated RP-HPLC Method for Simultaneous Estimation and Stability Study of Tegafur, Gimeracil and Oteracil in Combined Dosage Form - Ravisankar, Panchumarthy; Konidala, Sathish Kumar; Sri, Kamma Harsha; Kolakaluri, Chaitanya Sucharitha; Eswarudu, Munnangi Mukkanti; Chinni, Venkata Prasad Rao; Puttagunta, Srinivasa Babu (Indian Journal of Pharmaceutical Education and Research)
Aim: This study developed a validated and stability-analyzing Reverse-Phase High-Performance Liquid Chromatography (RP-HPLC) method for simultaneous determination of selected drugs Materials and Methods: Separation, quantification and degradation of the selected drugs and their degradation study was performed on Waters Alliance-e2695, with X Bridge phenyl column (150×4.6 mM, 3.5 μ) column, mixture of Acetonitrile (ACN) and 0.1% v/v trifluoroacetic acid (50:50% v/v) as mobile phase, flow rate of 1.0 mL/min at 244 nm under ambient temperature using PDA detector. Results: Tegafur, Gimeracil and Oteracil were separated effectively with retention times of 2.8, 7.5 and 9.5 min respectively. The optimized method was validated in different aspects as per the ICH Q1A(R2) guidelines. The method showed linear responses at 50-300 μg/mL (r2=0.99984), 14.50-87 μg/mL (r2=0.99930) and 39.50-237.00 μg/mL (r2=0.99980) for tegafur, gimeracil and oteracil, respectively. Results of inter- and intraday, robustness analysis in terms of %RSD were found to be less than 2.0%. Forced degradation analysis indicated that most of the forced degradation conditions induced impurities in the selected drugs, except for hydrolysis degradation. Conclusion: The results indicate that the method conditions are aligned with the ICH method validation limits. The forced degradation study results indicated that except in hydrolytic degradation, the drugs were degraded to produce impurities. Therefore, the developed method may be suitable for the simultaneous determination of the selected drugs in routine analysis.
Keywords: Gimeracil; Oteracil; RP-HPLC; Simultaneous; Stability studies; Tegafur.